Preparation method of BTA-ZIF-8 (at) Ce-MMT nano composite powder loaded with double corrosion inhibitors
By using double corrosion inhibitors to load BTA-ZIF-8@Ce-MMT nanocomposite powder in aqueous epoxy coatings, the problem of surface defects and local corrosion during curing and use of the aqueous epoxy coating is solved, and the active protection function and corrosion resistance of the coating are significantly improved.
Patent Information
- Application Number
- CN202411874662.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing aqueous epoxy coatings often have surface defects during curing and use, resulting in the penetration of corrosive media, which in turn triggers local corrosion reactions and ultimately loses the protective effect.
Using a double corrosion inhibitor to load BTA-ZIF-8@Ce-MMT nanocomposite powder, cerium ions are replaced between the montmorillonite layers through the cationic substitution characteristics of montmorillonite, and a zeolite imidazole coated with benzotriazole metal organic frame material (BTA-ZIF-8) is constructed on the surface of the two-dimensional slab of montmorillonite to improve the compatibility and protection of the coating.
The active protection function of the aqueous epoxy coating is realized. Through the synergistic effect of cerium ion and benzotriazole, the corrosion resistance and self-healing ability of the coating are significantly improved, and the service life of the coating is extended.
Smart Images

Figure CN119875415A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal protective coating materials, and in particular to a method for preparing a double corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder, aiming to impart an active protective function to a waterborne epoxy coating. Background Art
[0002] Metal corrosion is a major threat to the safety and life of infrastructure, and the economic losses caused by metal corrosion are also very large. Epoxy resin coating, as the main technical means of metal protection, relies on passive protection mechanisms to delay corrosion by forming a physical barrier between the metal surface and the corrosive environment. However, water-based epoxy coatings often have surface defects during curing and use, which lead to the penetration of corrosive media, which in turn triggers local corrosion reactions and eventually loses its protective effect. Therefore, in recent years, coating technology has gradually added active protection mechanisms to effectively increase the service life of the coating by adding corrosion inhibitors. When the coating is damaged or the metal surface is corroded, the corrosion inhibitor can passivate the metal surface or delay the corrosion reaction, thereby enhancing the self-healing ability of the coating and greatly increasing the service life of the coating.
[0003] Montmorillonite (MMT) is a natural silicate mineral. Due to its layered structure, good ion exchangeability and abundant resources, it is widely used in adsorption materials, catalyst carriers and drug delivery systems. In the field of metal protection, montmorillonite is often used as a coating filler to enhance the barrier properties of polymer coatings. However, since the surface of montmorillonite is rich in hydroxyl groups and has high polarity, and has poor compatibility with organic polymers, surface modification is usually required to enhance its corrosion protection performance in the coating. At present, research in academia and industry on the application of montmorillonite as a coating filler in active protection is still in a blank stage.
[0004] Benzotriazole (BTA) is a commonly used corrosion inhibitor and is widely used in metal protective coatings. It effectively slows down metal corrosion by forming a stable complex with metal ions. However, the amount of benzotriazole added is generally small (0.1-1%), because excessive addition can easily lead to agglomeration during the curing process of the coating, which in turn reduces the corrosion resistance of the coating.
[0005] Therefore, it is necessary to propose a new solution to solve the above technical problems. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a double corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder.
[0007] To solve the technical problem, the solution of the present invention is:
[0008] Provided is a method for preparing a dual corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder, comprising the following steps:
[0009] (1) Take dry montmorillonite and obtain MMT particles after ball milling;
[0010] (2) adding an appropriate amount of deionized water to the MMT particles in step (1), and allowing the particles to settle naturally after ultrasonic dispersion; taking the supernatant and setting it aside;
[0011] (3) adding cerium nitrate hexahydrate and an appropriate amount of deionized water to the supernatant of step (2), and reacting in a water bath at 25° C. with stirring for 24 hours;
[0012] (4) adding zinc nitrate hexahydrate to the reaction solution obtained in step (3) and stirring until it is completely dissolved;
[0013] (5) Add benzotriazole BTA and 2-methylimidazole to an appropriate amount of anhydrous ethanol and stir until completely dissolved;
[0014] (6) mixing the two solutions obtained in step (4) and step (5), and then reacting them in a water bath at 25° C. with stirring for 12 hours;
[0015] (7) centrifuging the reaction solution obtained in step (6), and washing and drying the precipitate to obtain BTA-ZIF-8@Ce-MMT nanocomposite powder;
[0016] Among the raw materials used in the above steps, the mass ratio of montmorillonite MMT, cerium nitrate hexahydrate, zinc nitrate hexahydrate, benzotriazole BTA and 2-methylimidazole is: 6-10: 0.1-0.2: 0.5-1.5: 0.3-0.96: 1-2.85.
[0017] As a preferred embodiment of the present invention, based on 6 to 10 parts by weight of montmorillonite MMT, the deionized water added in step (2) is 120 to 150 parts by weight, and 10 to 20 parts by weight of the supernatant is taken; the deionized water added in step (3) is 75 to 90 parts by weight; and the anhydrous ethanol added in step (5) is 25 to 40 parts by weight.
[0018] As a preferred embodiment of the present invention, in the step (1), the ball milling treatment time is 2 hours, the frequency of the driving motor is 45 Hz, and the rotation speed of the ball mill is 2700 rpm.
[0019] As a preferred embodiment of the present invention, in the step (2), ultrasonic dispersion is performed for 20 minutes, and natural sedimentation is performed for 24 hours, and the size of the MMT particles in the supernatant is ≤1 μm.
[0020] As a preferred embodiment of the present invention, the purity of the cerium nitrate hexahydrate, the zinc nitrate hexahydrate, the purity of benzotriazole BTA, 2-methylimidazole and anhydrous ethanol are all not less than 99.7%.
[0021] As a preferred embodiment of the present invention, in steps (3) to (6), the stirring speed is 750 rpm.
[0022] As a preferred embodiment of the present invention, in step (7), the speed of centrifugal separation is at least 5000 rpm and the time is at least 15 min; the speed of centrifugal washing is at least 5000 rpm and the time is at least 15 min; and the drying treatment is carried out in an oven at 60°C.
[0023] The present invention further provides an application method of the dual corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder prepared by the aforementioned method, which comprises adding the nanocomposite powder to a water-based epoxy resin anti-corrosion coating, wherein the mass ratio of the nanocomposite powder to the water-based epoxy resin anti-corrosion coating is 0.5%; after stirring evenly, covering the surface of the substrate with the mixed coating by spraying or coating; and curing at 150° C. for 1 hour to obtain a water-based epoxy resin anti-corrosion coating with an active protective function.
[0024] Description of the invention principle:
[0025] 1. Montmorillonite has excellent cationic intercalation properties, which enables it to insert corrosion inhibitors between layers. The use of this property to prepare nanocomposite powders not only has passive barrier functions, but also provides active protection. Chromium-containing corrosion inhibitors have significant effects in the field of metal protection, but their toxicity limits their application. Cerium ions and their compounds are considered to be environmentally friendly alternatives to chromates, which can provide cathodic protection by reacting with hydroxide ions to form protective films of cerium oxides and hydroxides. Cerium is an element with abundant reserves and low prices, which provides broad prospects for its application in the field of protection. Based on the above factors, the present invention utilizes the low-cost and abundant resource montmorillonite raw material to load cerium ions and benzotriazole dual corrosion inhibitors, and replaces the environmentally friendly cerium ions into the interlayer structure of the montmorillonite nano-two-dimensional sheet through the cation replaceable characteristics of montmorillonite; at the same time, an in-situ growth preparation method is used to construct a zeolite imidazole ester metal-organic framework material (BTA-ZIF-8) coated with benzotriazole on the surface of the montmorillonite two-dimensional sheet, and the nano-composite powder preparation technology is used to effectively improve the compatibility of the filler nano-composite powder and the water-based epoxy coating, so as to realize a nano-composite powder with both active protection and passive barrier functions, and use it in the water-based epoxy protective coating by trace addition to improve the coating performance.
[0026] The double corrosion inhibitor described in the present invention refers to benzotriazole and cerium ions.
[0027] 2. Montmorillonite (MMT) is a natural silicate clay mineral with a layered structure. It has two layers of silicon-oxygen tetrahedrons sandwiched between aluminum-oxygen octahedra and has exchangeable interlayer cation characteristics. Due to its abundant natural resources, montmorillonite is low-cost. Its two-dimensional layered structure can effectively act as a barrier to corrosive media in coatings, but due to its high surface polarity and large particle size, it has poor compatibility with organic polymers.
[0028] Zeolite imidazolate framework material (ZIF-8) is a metal organic framework material (MOFs) with adjustable pore size, low toxicity, good chemical stability and acid sensitivity. It is widely used in biomedicine, wastewater treatment, catalyst and protection fields. Due to the difference in application methods, there is no public record of the composite application of ZIF-8 and montmorillonite.
[0029] The present invention combines montmorillonite with BTA-loaded ZIF-8 nanoparticles after ball milling to construct a nanocomposite powder. ZIF-8 particles are synthesized in situ on montmorillonite by a one-step method, which not only gives the composite material active protection and passive barrier functions, but also improves the surface polarity of montmorillonite through the growth of ZIF-8 particles, increases the specific surface area, and thus improves its compatibility in organic polymers. This method has not been reported in the relevant field.
[0030] 3. The present invention innovatively proposes to introduce cerium ions with corrosion inhibition function as guests into the interlayer of montmorillonite particles by cation exchange method to obtain Ce-MMT two-dimensional material. Cerium is one of the most abundant rare earth elements in the earth's crust and its resources are abundant. Inserting cerium ions into the interlayer of montmorillonite by cation exchange not only makes it have active protection function, but also provides cathodic protection when the corrosive medium corrodes the substrate. The preparation process of the present invention is simple, and only requires stirring reaction at room temperature, which greatly reduces energy consumption, and the raw materials are abundant and low in cost. No toxic substances are produced during the preparation process, which meets the requirements of green environmental protection.
[0031] 4. The present invention further innovatively loads the corrosion inhibitor BTA molecule as the second ligand in the skeleton structure of ZIF-8, so that it has a pH response function and realizes the controlled release of the corrosion inhibitor. This can avoid the problem of the corrosion inhibitor being directly introduced into the protective coating, which leads to the degradation of the coating performance. In addition, after the surface of the ZIF-8 microspheres is modified by the montmorillonite two-dimensional nanosheet layer, the compatibility of the powder and the coating can be improved, and the uniform distribution in the coating can be achieved, and the gaps and holes generated by the volatilization of the solvent during the curing of the water-based epoxy resin can be filled, and the generation of microcracks and defects in the coating can be reduced.
[0032] 5. The active defense mechanism of the product of the present invention at the microscopic level is as follows:
[0033] As the use time of waterborne epoxy protective coating increases, defects such as cracks and micropores on the coating surface increase, forming corrosion channels and accelerating the invasion of corrosive media. The two-dimensional structure of montmorillonite in the nanocomposite powder can extend the diffusion path of the corrosive medium and play a passive protective role. At the same time, when corrosion reaches the metal surface, the micro-area electrochemical reaction caused by the micro-area causes the pH value of the anode area to decrease, causing the ZIF-8 skeleton to collapse, releasing BTA molecules to complex with iron ions, forming an inhibitory film to prevent corrosion from further eroding the metal surface. In addition, the hydroxide ions in the cathode area react with cerium ions to form a cerium hydroxide or cerium oxide deposition film, thereby providing active protection.
[0034] The specific implementation in the actual application scenario is: adding 0.5% by mass of BTA-ZIF-8@Ce-MMT nanocomposite powder to the water-based epoxy coating, spraying it on the metal substrate, and realizing the active and passive dual protection functions of the coating. Therefore, the technology of the present invention breaks through the traditional idea of existing two-dimensional materials and core-shell structure nanocomposite split applications.
[0035] Compared with other existing types of waterborne epoxy coating active protective functional materials, the present invention has the following beneficial effects:
[0036] 1. The nanocomposite powder prepared by the technology of the present invention is loaded with cerium ions and benzotriazole dual corrosion inhibitors, which can simultaneously achieve corrosion inhibition in the anode area and the cathode area in the corrosion reaction micro-area, further improving the active protection effect of the powder.
[0037] 2. In the preparation process of the present invention, the required reaction conditions are only room temperature conditions. By utilizing the characteristics of the raw materials, the final nanocomposite powder is synthesized in situ through cation exchange and a one-step method. No additional reaction conditions and loading steps such as heating and pressurization are required, thereby simplifying the synthesis process.
[0038] 3. The nanocomposite powder prepared by the present invention has good dispersibility in water-based epoxy coatings and is not easy to agglomerate, thus expanding the application scope of montmorillonite two-dimensional sheet materials in the field of protection.
[0039] 4. The montmorillonite and cerium element used in the present invention are both natural mineral resources with relatively abundant reserves, which not only reduces the preparation cost but also broadens the application scope of rare earth elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a scanning electron microscope image (5000 times) of the montmorillonite two-dimensional material MMT in the supernatant after ball milling and natural sedimentation in deionized water.
[0041] Figure 2 This is a scanning electron microscope image (20,000 times) of BTA-ZIF-8@Ce-MMT nanocomposite powder.
[0042] Figure 3 It is the nitrogen adsorption-desorption curve of BTA-ZIF-8@Ce-MMT nanocomposite powder.
[0043] Figure 4 It is the pore size distribution diagram of BTA-ZIF-8@Ce-MMT nanocomposite powder.
[0044] Figure 5 This is the release curve of the corrosion inhibitor BTA of BTA-ZIF-8@Ce-MMT nanocomposite powder at different times and different pH values.
[0045] Figure 6 This is the release concentration diagram of the corrosion inhibitor cerium ions of BTA-ZIF-8@Ce-MMT nanocomposite powder at different time points and different pH values.
[0046] Figure 7 Electrochemical impedance spectra of waterborne epoxy protective coatings without corrosion inhibitor, with 0.5% MMT, and with 0.5% BTA-ZIF-8@Ce-MMT nanocomposite powder after immersion in 3.5% NaCl solution for 28 days.
[0047] Figure 8 This is a graph showing the adhesion changes of water-based epoxy protective coatings without corrosion inhibitor, with 0.5% MMT, and with 0.5% BTA-ZIF-8@Ce-MMT nanocomposite powder before and after immersion in a salt spray chamber for two weeks. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with specific embodiments and drawings.
[0049] 1. Summary of the implementation scheme of the present invention:
[0050] Preparation steps of dual corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder:
[0051] (1) Dry montmorillonite is ball-milled to obtain MMT particles; as an example, the ball-milling time is 2 hours, the frequency of the driving motor is 45 Hz, and the speed of the ball mill is 2700 rpm;
[0052] (2) Add an appropriate amount of deionized water to the MMT particles in step (1), disperse by ultrasonication for 20 minutes, and allow to settle naturally for 24 hours. Take the supernatant for later use. The MMT particle size in the supernatant is ≤1 μm;
[0053] Through the operation of steps (1) and (2), the montmorillonite presents a more two-dimensional layered structure, creating conditions for the subsequent cerium ion replacement and in-situ growth to prepare metal organic framework materials. The supernatant is taken because large-sized montmorillonite will produce sedimentation, and the montmorillonite particles contained in the supernatant are smaller in size, which is more conducive to the subsequent dispersion of particles in the water-based epoxy coating.
[0054] (3) adding cerium nitrate hexahydrate and an appropriate amount of deionized water to the supernatant of step (2), and reacting in a water bath at 25° C. with stirring for 24 hours;
[0055] Through the operation of this step, due to the excellent cation interlayer exchange characteristics of montmorillonite, the cerium ions are replaced into the interlayer of montmorillonite through ion exchange reaction, which promotes the addition of the first corrosion inhibitor cerium ions into the particles.
[0056] (4) adding zinc nitrate hexahydrate to the reaction solution obtained in step (3) and stirring until it is completely dissolved;
[0057] (5) Add benzotriazole BTA and 2-methylimidazole to an appropriate amount of anhydrous ethanol and stir until completely dissolved;
[0058] (6) mixing the two solutions obtained in step (4) and step (5), and then reacting them in a water bath at 25° C. with stirring for 12 hours;
[0059] Through the operation of steps (4)(5)(6), a MOF structure ZIF-8 of zinc ions and imidazole ligands is synthesized on the montmorillonite layered structure by a one-step method, and a second corrosion inhibitor benzotriazole is coated therein and directly added in the form of a second ligand.
[0060] (7) The reaction solution obtained in step (6) is centrifuged, and the precipitate is centrifugally washed and dried to obtain BTA-ZIF-8@Ce-MMT nanocomposite powder; the speed of the centrifugal separation is at least 5000 rpm and the time is at least 15 min; the speed of the centrifugal washing is at least 5000 rpm and the time is at least 15 min; the drying treatment is drying in an oven at 60°C.
[0061] Through the operation of this step, the dry powder of the final particles BTA-ZIF-8@Ce-MMT was obtained, ready for the subsequent spraying in water-based epoxy coating.
[0062] Among the raw materials used in the above steps, the mass ratio of montmorillonite MMT, cerium nitrate hexahydrate, zinc nitrate hexahydrate, benzotriazole BTA and 2-methylimidazole is: 6-10: 0.1-0.2: 0.5-1.5: 0.3-0.96: 1-2.85. Based on 6-10 mass parts of montmorillonite MMT, 120-150 mass parts of deionized water are added in step (2), and 10-20 mass parts of supernatant are taken; 75-90 mass parts of deionized water are added in step (3); and 25-40 mass parts of anhydrous ethanol are added in step (5). The purity of the cerium nitrate hexahydrate, zinc nitrate hexahydrate, benzotriazole BTA, 2-methylimidazole and anhydrous ethanol are not less than 99.7%. In the steps (3) to (6), the stirring speed is 750rpm.
[0063] 2. Application method of double corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder:
[0064] (1) Add the nanocomposite powder to the waterborne epoxy resin anticorrosion coating, stir evenly and set aside. The mass ratio of the nanocomposite powder to the waterborne epoxy resin anticorrosion coating is 0.5%.
[0065] (2) Spraying or coating the mixed coating on the surface of the substrate; curing the mixed coating at 150° C. for 1 hour to obtain a water-based epoxy resin anti-corrosion coating with active protective function.
[0066] The coverage thickness of spraying or coating can be determined according to the requirements of the actual application scenario and the characteristics of the water-based epoxy resin anti-corrosion coating itself.
[0067] 2. Embodiment Content
[0068] In the following examples, the montmorillonite used is a product of Shanghai MacLean Biochemical Technology Co., Ltd., benzotriazole and 2-methylimidazole are products of Aladdin Industries, and anhydrous ethanol, zinc nitrate hexahydrate, and cerium nitrate hexahydrate are products of Sinopharm Chemical Reagent Co., Ltd. The bentonite particle size is ≤25 μm, the purity of BTA is at least 99%, the purity of 2-methylimidazole is at least 98%, the purity of anhydrous ethanol is at least 99.7%, the purity of zinc nitrate hexahydrate is at least 99%, and the purity of cerium nitrate hexahydrate is at least 99%.
[0069] Unless otherwise specified, the following percentages are all mass percentages, and the numbers are all mass numbers. The operating conditions not described in the examples are all performed according to the contents described in the previous implementation scheme overview.
[0070] Example 1
[0071] (1) ball-milling 6 parts by weight of dried montmorillonite for 2 hours to obtain montmorillonite particles;
[0072] (2) adding 120 parts by weight of deionized water to the montmorillonite particles in step (1), dispersing by ultrasonic for 20 minutes, and then allowing the particles to settle naturally for 24 hours, and taking the supernatant for later use;
[0073] (3) adding 0.1 parts by mass of cerium nitrate hexahydrate to 10 parts by mass of the supernatant obtained in step (2), and adding 75 parts by mass of deionized water, and stirring the reaction in a water bath at 25° C. for 24 hours;
[0074] (4) adding 0.5 parts by mass of zinc nitrate hexahydrate to the solution obtained in step (3) and stirring until completely dissolved;
[0075] (5) Add 0.3 parts by mass of benzotriazole and 1 part by mass of 2-methylimidazole to 25 parts by mass of anhydrous ethanol and stir until completely dissolved;
[0076] (6) mixing the solution obtained in step (4) with the solution obtained in step (5), and stirring the mixture in a water bath at 25° C. for 12 hours;
[0077] (7) separating the mixed solution obtained in step (6) by a centrifuge, washing the obtained precipitate by centrifugation with deionized water, and drying it in an oven at 60° C. to obtain a BTA-ZIF-8@Ce-MMT nanocomposite powder;
[0078] Example 2
[0079] (1) ball-milling 8 parts by weight of dried montmorillonite for 2 hours to obtain montmorillonite particles;
[0080] (2) adding 135 parts by weight of deionized water to the montmorillonite particles in step (1), dispersing by ultrasonic for 20 minutes, and then allowing the particles to settle naturally for 24 hours, and taking the supernatant for later use;
[0081] (3) adding 0.16 parts by mass of cerium nitrate hexahydrate to 14 parts by mass of the supernatant obtained in step (2), and adding 87.5 parts by mass of deionized water, and stirring the reaction in a water bath at 25° C. for 24 hours;
[0082] (4) adding 0.95 parts by mass of zinc nitrate hexahydrate to the solution obtained in step (3) and stirring until completely dissolved;
[0083] (5) Add 0.5 parts by mass of benzotriazole and 1.8 parts by mass of 2-methylimidazole to 32 parts by mass of anhydrous ethanol and stir until completely dissolved;
[0084] (6) mixing the solution obtained in step (4) with the solution obtained in step (5), and stirring the mixture in a water bath at 25° C. for 12 hours;
[0085] (7) separating the mixed solution obtained in step (6) by a centrifuge, washing the obtained precipitate by centrifugation with deionized water, and drying it in an oven at 60° C. to obtain a BTA-ZIF-8@Ce-MMT nanocomposite powder;
[0086] Example 3
[0087] (1) ball-milling 10 parts by weight of dried montmorillonite for 2 hours to obtain montmorillonite particles;
[0088] (2) adding 150 parts by weight of deionized water to the montmorillonite particles in step (1), dispersing by ultrasonic for 20 minutes, and then allowing the particles to settle naturally for 24 hours, and taking the supernatant for later use;
[0089] (3) adding 0.2 parts by mass of cerium nitrate hexahydrate to 20 parts by mass of the supernatant obtained in step (2), and adding 90 parts by mass of deionized water, and stirring the reaction in a water bath at 25° C. for 24 hours;
[0090] (4) adding 1.5 parts by mass of zinc nitrate hexahydrate to the solution obtained in step (3) and stirring until completely dissolved;
[0091] (5) adding 0.96 parts by mass of benzotriazole and 2.85 parts by mass of 2-methylimidazole to 40 parts by mass of anhydrous ethanol and stirring until completely dissolved;
[0092] (6) mixing the solution obtained in step (4) with the solution obtained in step (5), and stirring the mixture in a water bath at 25° C. for 12 hours;
[0093] (7) separating the mixed solution obtained in step (6) by a centrifuge, washing the obtained precipitate by centrifugation with deionized water, and drying it in an oven at 60° C. to obtain a BTA-ZIF-8@Ce-MMT nanocomposite powder;
[0094] 3. Product performance and comparative experimental analysis of the examples
[0095] Figure 1 The scanning electron microscope image in the figure shows that the ball-milled montmorillonite presents a two-dimensional layered structure and the particles are cross-linked together, indicating that MMT has a high surface polarity.
[0096] Figure 2 It is a scanning electron microscope image of BTA-ZIF-8@Ce-MMT nanocomposite powder, showing an overall flaky structure with the surface covered with rhombic dodecahedral BTA-ZIF-8 nanoparticles with a particle size of about 350 to 600 nm.
[0097] Figure 3 , 4The nitrogen adsorption curve and pore size distribution of BTA-ZIF-8@Ce-MMT nanocomposite powder. It can be seen from the figure that the nanocomposite powder has a high specific surface area of 663m 2 / g, the average pore size is about 0.4nm, and the specific surface area of MMT is significantly improved.
[0098] Figure 5 The release curve of the corrosion inhibitor BTA in BTA-ZIF-8@Ce-MMT nanocomposite powder at different times shows that from pH = 7 to pH = 3, as the acidity increases, the release rate of the corrosion inhibitor gradually increases, and the final release concentration also gradually increases. The release of BTA shows a strong acid response release behavior.
[0099] Figure 6 This is the release concentration diagram of the corrosion inhibitor cerium ion of BTA-ZIF-8@Ce-MMT nanocomposite powder at different time points. The cerium ion initially exhibits acid response properties, but as time goes by, the solution gradually penetrates into the MMT interlayer, promoting the escape of the cerium ion, and finally the cerium ion concentration at each pH point remains consistent.
[0100] Comparative experiment 1
[0101] 1. Using Q235 carbon steel sandblasted with 200 mesh glass sand as the substrate, a water-based epoxy protective coating without adding a corrosion inhibitor, a water-based epoxy protective coating adding 0.5% MMT, and a water-based epoxy protective coating adding 0.5% BTA-ZIF-8@Ce-MMT nanocomposite powder in Example 1 were sprayed on the substrate, with a spraying thickness of about 25 μm; after curing at 150° C. for 1 hour, the electrochemical impedance spectra of the coating immersed in 3.5% sodium chloride solution for different immersion times were collected, as shown in FIG. Figure 7 shown.
[0102] 2. Compare the electrochemical impedance spectra of the surfaces of the samples after being immersed in sodium chloride solution for different periods of time. Figure 6 The comparison results show that the electrochemical impedance of the protective coating with nanocomposite powders remains stable even after 28 days of immersion, while the electrochemical impedance of the protective coatings without and with MMT has dropped by an order of magnitude, which is due to defects such as pores generated during the curing process of the waterborne epoxy coating and the incompatibility of MMT with the waterborne epoxy coating. It can be seen that the nanocomposite powders of the present invention can improve the corrosion resistance of the waterborne epoxy coating in a long-term manner.
[0103] Comparative experiment 2
[0104] 1. Using Q235 carbon steel sandblasted with 200 mesh glass sand as the substrate, the water-based epoxy protective coating with no addition, 0.5% MMT addition, and 0.5% BTA-ZIF-8@Ce-MMT nanocomposite powder added in Example 1 was sprayed on the substrate, with a spraying thickness of about 25 μm; after curing at 150° C. for 1 hour, an adhesion test was performed, and then the adhesion test was performed after being placed in a neutral salt spray box for two weeks. Figure 7 shown.
[0105] 2. Compare the adhesion of each coating before immersion in salt spray, see Figure 8 . The adhesion strength of the coatings with the addition of nanocomposite powders is improved to a certain extent. After two weeks of immersion, the coating with 0.5% MMT added has the highest adhesion decrease rate of 77%. The coating with 0.5% BTA-ZIF-8@Ce-MMT nanocomposite powder added in Example 1 has the lowest adhesion decrease rate of 50.8%, and the adhesion is improved by 75% compared with the blank coating. It can be seen that the nanocomposite powder of the present invention can significantly improve the dispersibility of MMT in water-based epoxy coatings and enhance the protective performance of the coating.
Claims
1. A method for preparing a dual corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder, characterized in that: The following steps are involved: (1) Take dry montmorillonite and obtain MMT particles after ball milling; (2) adding an appropriate amount of deionized water to the MMT particles in step (1), and allowing the particles to settle naturally after ultrasonic dispersion; taking the supernatant and setting it aside; (3) adding cerium nitrate hexahydrate and an appropriate amount of deionized water to the supernatant of step (2), and reacting in a water bath at 25° C. with stirring for 24 hours; (4) adding zinc nitrate hexahydrate to the reaction solution obtained in step (3) and stirring until it is completely dissolved; (5) Add benzotriazole BTA and 2-methylimidazole to an appropriate amount of anhydrous ethanol and stir until completely dissolved; (6) mixing the two solutions obtained in step (4) and step (5), and then reacting them in a water bath at 25° C. with stirring for 12 hours; (7) centrifuging the reaction solution obtained in step (6), and washing and drying the precipitate to obtain BTA-ZIF-8@Ce-MMT nanocomposite powder; Among the raw materials used in the above steps, the mass ratio of montmorillonite MMT, cerium nitrate hexahydrate, zinc nitrate hexahydrate, benzotriazole BTA and 2-methylimidazole is: 6-10: 0.1-0.2: 0.5-1.5: 0.3-0.96: 1-2.
85.
2. The method according to claim 1, characterized in that Based on 6 to 10 parts by weight of montmorillonite MMT, the amount of deionized water added in step (2) is 120 to 150 parts by weight, and 10 to 20 parts by weight of the supernatant is taken; the amount of deionized water added in step (3) is 75 to 90 parts by weight; and the amount of anhydrous ethanol added in step (5) is 25 to 40 parts by weight.
3. The method according to claim 1, characterized in that In the step (1), the ball milling treatment time is 2 hours, the frequency of the driving motor is 45 Hz, and the rotation speed of the ball mill is 2700 rpm.
4. The method according to claim 1, characterized in that: In the step (2), ultrasonic dispersion is performed for 20 minutes and natural sedimentation is performed for 24 hours; the size of the MMT particles in the supernatant is ≤1 μm.
5. The method according to claim 1, characterized in that The purity of the cerium nitrate hexahydrate, the zinc nitrate hexahydrate, the purity of benzotriazole BTA, 2-methylimidazole and anhydrous ethanol are all not less than 99.7%.
6. The method according to claim 1, characterized in that In steps (3) to (6), the stirring speed is 750 rpm.
7. The method according to claim 1, characterized in that In the step (7), the speed of centrifugal separation is at least 5000 rpm and the time is at least 15 min; the speed of centrifugal washing is at least 5000 rpm and the time is at least 15 min; and the drying treatment is carried out in an oven at 60°C.
8. The application method of the dual corrosion inhibitor loaded BTA-ZIF-8@Ce-MMT nanocomposite powder prepared by the method described in any one of claims 1 to 7, characterized in that: The method comprises adding the nano-composite powder to a water-based epoxy resin anti-corrosion coating, wherein the mass ratio of the nano-composite powder to the water-based epoxy resin anti-corrosion coating is 0.5%; after being stirred evenly, the mixed coating is covered on the surface of a substrate by spraying or coating; and curing the mixed coating at 150° C. for 1 hour to obtain a water-based epoxy resin anti-corrosion coating with an active protective function.
Citation Information
Patent Citations
Preparation method of corrosion inhibitor@cerium dioxide microcapsule for anticorrosive paint
CN113083175A
Preparation method of corrosion inhibitor loaded BTA (at) ZIF-8 / BN-OH composite powder
CN115353763A
Preparation method of self-repairing anti-corrosion coating based on ZIFs
CN116004086A
Process for producing particles of amine reaction product
EP0971021A1
Process for producing particles of amine reaction product
EP1067173A1